DISCOVERING PIERCE’S TRICHOTOMIES IN THE ANIMATED CHARACTERS OF PETER SOHN’S FILM “ELEMENTAL: FORCE OF NATURE” AS THE REPRESENTATION OF THE ELEMENTS OF NATURE - Anastasia, Happy (LPPM STISIPOL Mujahiddin, 2025)
This study explores the application of Charles Sanders Pierce’s semiotic trichotomy in the animated characters of Peter Sohn’s Elemental: Force of Nature. The film presents personified representations of natural elements such as fire, water, air, and earth, through the main characters, reflecting the traits and dynamics of each element. The method is qualitative, while the data are taken from some pictures in the scenes. The data are analyzed through: data reduction, data display, and verification. As the results, dealing with the elements of fire: 15 data, the elements of water: 10 data, the elements of air: 4 data, and the elements of soil: 5 data. As the conclusions, the analysis reveals that Pierce’s three categories of signs form a visual and cultural communication pattern that illustrates humanity’s relationship with nature. This study contributes to a deeper understanding of ecological representation in animated media and expands the application of semiotic theory in film studies